2023
DOI: 10.1177/08839115221149725
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of apigenin-loaded chitosan/gelatin membranes for bone tissue engineering applications

Abstract: Fabricating degradable polymer-based membranes has attracted much attention for guided bone regeneration. Chitosan/gelatin (Cs/Gel) composites are among the most known scaffolds with structural similarity to bone matrix and a high potential to support cell attachment and proliferation. Recently, plant-derived phenolic compound apigenin has been identified to direct the osteogenic differentiation of mesenchymal stem cells and retain osteoblast metabolic functions. We incorporated apigenin into Cs/Gel membranes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The Saos-2 osteoblasts were cultured on membranes to examine the cell–membrane interaction, viability, proliferation, and mineralization under the osteogenic culture condition. Based on the findings, study data suggested that Cs/Gel membranes loaded with low apigenin contents could enhance the survival, proliferation, and mineralization of osteoblasts [ 217 ]. The newly developed encapsulated Ap (Ap-CH-BSA-FANPs) was characterized as well as tested in vitro.…”
Section: Nanoformulation Of Apigenin and Pharmacological Actionmentioning
confidence: 99%
“…The Saos-2 osteoblasts were cultured on membranes to examine the cell–membrane interaction, viability, proliferation, and mineralization under the osteogenic culture condition. Based on the findings, study data suggested that Cs/Gel membranes loaded with low apigenin contents could enhance the survival, proliferation, and mineralization of osteoblasts [ 217 ]. The newly developed encapsulated Ap (Ap-CH-BSA-FANPs) was characterized as well as tested in vitro.…”
Section: Nanoformulation Of Apigenin and Pharmacological Actionmentioning
confidence: 99%
“…The main factors determining SC differentiation are extracellular matrix (ECM) components, cell‐ECM, cell‐cell interactions, and soluble bioactive factors 10 . Regarding the importance of ECM in regulating cell behavior, tissue engineering and regenerative medicine (TERM) assemble cells, scaffolds, and biomolecules as artificial biomimetic constructs that replace or accelerate the regeneration of damaged tissues 11 . Decellularized tissues are favorable options for scaffold fabrication because they mimic the morphological, compositional, and biomechanical cues of native tissues 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…10 Regarding the importance of ECM in regulating cell behavior, tissue engineering and regenerative medicine (TERM) assemble cells, scaffolds, and biomolecules as artificial biomimetic constructs that replace or accelerate the regeneration of damaged tissues. 11 Decellularized tissues are favorable options for scaffold fabrication because they mimic the morphological, compositional, and biomechanical cues of native tissues. 12,13 Amniotic membrane (AM) is the biological waste of labor and an accessible source of ECM rich in collagens, laminin, fibronectin, hyaluronic acid, and growth factors.…”
mentioning
confidence: 99%
“…Cs is a proper candidate for wound healing because it is cost-benefit, non-toxic, biocompatible, biodegradable, and mucoadhesive. 3 Also, Cs is highly helpful in hindering bacterial, fungal, and viral infections and absorbing water and biological fluids. 4 Eugenol (phenylpropanoid) is a herbal phenolic compound isolated from essential oils of the Lamiaceae, Lauraceae, Myrtaceae, and Myristicaceae families and abundantly found in clove oil (Syzygium aromaticum).…”
Section: Introductionmentioning
confidence: 99%
“…Cs is a proper candidate for wound healing because it is cost-benefit, non-toxic, biocompatible, biodegradable, and mucoadhesive. 3 Also, Cs is highly helpful in hindering bacterial, fungal, and viral infections and absorbing water and biological fluids. 4…”
Section: Introductionmentioning
confidence: 99%